Rancang Bangun Aplikasi Desktop Pendeteksi Duplikat Data NIK dan NKK pada File Excel Menggunakan Metode Exact Matching Berbasis Flutter - Ardhi Feisal Wijayanto; Rina Firliana; Dwi Harini (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2026)
The management of UMKM assistance recipient data at the Cooperatives and Micro Enterprises Office of Kediri Regency is still carried out manually using Microsoft Excel, resulting in frequent data duplication in the NIK and NKK columns. Excel's limitation of accurately processing only up to 15 digits is a serious obstacle because NIK consists of 16 digits, risking digit truncation that causes data inaccuracy and inaccurate aid distribution. This study aims to design and build a Flutter-based desktop application capable of detecting duplicate NIK or NKK data automatically, accurately, and informatively. The method used is Research and Development (R&D) with the Sugiyono development model simplified into eight stages, along with the Exact Matching algorithm based on HashMap which has O(n) time complexity. System testing was conducted using the Black Box Testing method through ten test scenarios covering file validation, NIK/NKK duplicate detection, result export, and application reset. The results showed that the application successfully detected all duplicate data with 100% accuracy and was able to process Excel files containing 5,000 rows of data in less than 1 second, much faster than the manual method which takes 2 to 3 hours. All ten Black Box Testing scenarios were declared successful (100% pass rate). The implication of this research is the availability of an appropriate technical solution that can be directly used by staff to accelerate data validation, and can serve as a reference for developing similar systems in other government institutions facing similar data duplication problems.